Efecto de Guatteria Gaumeri en pacientes con Hipertrigliceridemia - Meza González, Francisco Daniel (Universidad Autónoma Metropolitana, 2017)
Introduction. Dyslipidemias represent several pathological conditions where the main characteristic is the alteration of the lipid metabolism, with alterations of lipid and lipoprotein blood concentrations. Dyslipidemias condition cardiovascular disease that occupies the first place of world and national mortality. Atherogenic dyslipidemia and other factors, are part of the metabolic syndrome, which affects risk of heart disease and diabetes mellitus type 2. Therefore, it is proposed to Guatteria gaumeri, an endemic plant in the state of Yucatan, as a therapeutic option for hypertriglyceridemia, which has With a history of empirical medical practice and research studies of extract prepared with the cortex, on the effects on blood lipids and other effects of medical interest. Objective. To evaluate the effect of Guatteria gaumeri in patients with hypertriglyceridemia. Material and methods. A prospective, longitudinal, comparative experimental and open study was conducted with 62 patients (34 females and 28 males) between 19-77 years of age, Pachuca, Hidalgo, blood glucose levels, total cholesterol and triacylglycerols were determined and randomly integrated two groups of 31 patients each; one group was treated with Guatteria gaumeri Ø and the other with bezafibrate 200 mg tablets, both orally, for two months. At the end, blood levels of the biochemical parameters were again quantified. The data obtained before and after treatment of both groups were statistically compared and statistical significance was considered with a value of α <0.05. Results. Glucose and triacylglycerol levels decreased in both study groups, glucose in the problem group 12.8% (p = 0.032); and triacylglycerols in the problem group 16.8% (p = 0.011); Blood levels of total cholesterol were modified in the control group but not in the problem group (p = 0.415). Conclusions. Administration of Guatteria gaumeri Ø reduced blood glucose and triacylglycerol levels in patients with hypertriglyceridemia; Did not reduce blood levels of total cholesterol in these patients. Key words: Dyslipidemia, hypertriglyceridemia, triacylglycerols, lipids, Guatteria gaumeri; Introducción. Las dislipidemias representan diversas condiciones patológicas donde la característica principal es la alteración del metabolismo de los lípidos, con alteración de concentraciones de lípidos y lipoproteínas sanguíneos. Las dislipidemias condicionan enfermedad cardiovascular que ocupa el primer lugar de mortalidad mundial y nacional. La Dislipidemia aterogénica y otros factores, forman parte del síndrome metabólico, que condiciona riesgo cardíaco y diabetes mellitus tipo 2. Por tal motivo, se propone a Guatteria gaumeri, una planta endémica del estado de Yucatán, como opción terapéutica para hipertrigliceridemia, la cual cuenta con antecedentes de práctica médica empírica y con estudios de investigación del extracto preparado con la corteza, sobre los efectos en los lípidos sanguíneos y otros efectos de interés médico. Objetivo. Evaluar el efecto de Guatteria gaumeri en pacientes con hipertrigliceridemia. Material y métodos. Se realizó un estudio prospectivo, longitudinal, comparativo, experimental y abierto, con 62 pacientes (34 mujeres y 28 hombres) entre 19-77 años de edad, de Pachuca de Soto, Hidalgo, se determinaron niveles sanguíneos de glucosa, colesterol total y triacilgliceroles e integraron aleatoriamente dos grupos de 31 pacientes cada uno; un grupo fue tratado con Guatteria gaumeri Ø y el otro con bezafibrato 200 mg tabletas, ambos vía oral, durante dos meses. Al término se cuantificaron nuevamente niveles sanguíneos de los parámetros bioquímicos. Los datos obtenidos antes y después del tratamiento de ambos grupos se compararon estadísticamente y se consideró significancia estadística con un valor de α < 0.05. Resultados. Los niveles de glucosa y triacilgliceroles disminuyeron en ambos grupos del estudio, glucosa en el grupo problema 12.8% (p= 0.032); y triacilgliceroles en el grupo problema 16.8% (p= 0.011); los niveles sanguíneos de colesterol total se modificaron en el grupo control pero no en el grupo problema (p=0.415). Conclusiones. La administración de Guatteria gaumeri Ø redujo los niveles de glucosa y triacilgliceroles sanguíneos en pacientes con hipertrigliceridemia; no redujo los niveles sanguíneos de colesterol total en estos pacientes. Palabras clave: Dislipidemia, hipertrigliceridemia, triacilgliceroles, lípidos, Guatteria gaumeri